2016
DOI: 10.1039/c5nr08614k
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study of the nickel-catalyzed transformation of amorphous carbon into graphene in rapid thermal processing

Abstract: Ab initio molecular dynamics (AIMD) simulations are employed to investigate the chemical mechanism underlying the Ni-catalyzed transformation of amorphous carbon (a-C) into graphene in the rapid thermal processing (RTP) experiment to directly grow graphene on various dielectric surfaces via the evaporation of surplus Ni and C at 1100 °C (below the melting point of bulk Ni). It is found that the a-C-to-graphene transformation entails the metal-induced crystallization and layer exchange mechanism, rather than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 53 publications
1
24
0
1
Order By: Relevance
“…In a wider context, our study also contributes to the elucidation of the recently debated role of Ni 3 C as a possible intermediate bulk catalyst phase in Ni-catalyzed graphene 35 44 and carbon nanotube (CNT) 45 60 growth. Taking our Ni 3 C/a-C nanocomposites as a model system for graphitization from Ni 3 C, our in situ derived findings suggest that fcc Ni with interstitial carbon dissolved (Ni(-C)), rather than bulk Ni 3 C, is the active catalyst phase during graphitic nanostructure growth under typical chemical vapor deposition (CVD) conditions.…”
Section: Introductionmentioning
confidence: 84%
“…In a wider context, our study also contributes to the elucidation of the recently debated role of Ni 3 C as a possible intermediate bulk catalyst phase in Ni-catalyzed graphene 35 44 and carbon nanotube (CNT) 45 60 growth. Taking our Ni 3 C/a-C nanocomposites as a model system for graphitization from Ni 3 C, our in situ derived findings suggest that fcc Ni with interstitial carbon dissolved (Ni(-C)), rather than bulk Ni 3 C, is the active catalyst phase during graphitic nanostructure growth under typical chemical vapor deposition (CVD) conditions.…”
Section: Introductionmentioning
confidence: 84%
“…In fact, it has been shown that Ni particles can catalyze the conversion of amorphous to graphitic carbon at temperatures of 550 C resulting in disordered graphite layers on the particle surface. 29,30 Indeed, in the present study, bacterial cellulose in presence of Ni(OH) 2 decomposed about 70 C below the decomposition temperature of pure bacterial cellulose, which is a strong indication of the catalytic activity of the in situ formed nickel species, i.e. NiO and Ni.…”
Section: Synthesis and Characterization Of Carbon-nickel Hybrid Matermentioning
confidence: 46%
“…Amorphous carbon is a type of carbon that does not have any crystalline structure and contains a random distribution of sp 2 , sp 3 , and dangling bonds, so it is considered a completely isotropic material . Unlike anisotropic carbon materials such as CNTs, graphene, or graphite, the thermal conductivity of amorphous carbon in all directions is approximately the same .…”
Section: Carbon‐based Materials For Photothermal Actuator Designmentioning
confidence: 99%